Daya Tarik Perusahaan dan Kompetensi Karir yang Memengaruhi Niat Melamar Pekerjaan pada Mahasiswa Tingkat Akhir - Gia Rizky; Dwi Utami Puterisari; Yuni Putri Yustisi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study was to identify organizational attribute factors dan individual career competence to intention of applying for a job. This was a quantitavie research approach, using questionnaire as primary data method. There were 80 final students in DIY province as respondents. Research model and hypotheses were tested using IBM SPSS 23. To find out the main attributes of interest in applying for a job, mean arithmetic was conducted for each indicator in the dependent variables. The attractiveness of the company affected the intention of applying for a job, but career competence did not. Simultaneously, the attractiveness of the company and career competence affected the intention to apply for a job. The attribute of attractiveness of the company that is the highest value of the arithmetic mean is working conditions. As for the attributes of career competence with the highest arithmetic mean value is self-knowledge.